Pengaruh Disiplin Kerja, Job Description, dan Fasilitas Kerja Terhadap Prestasi Kerja Karyawan pada CV. Sakura Makmur Santoso - Lina Afifah; Kusuma Chandra Kirana (Politeknik Bisnis Indonesia, 2021)
This research was conducted to determine the effect of work discipline, job description and work facilities on work employee performance at CV. Sakura Makmur Santoso, Magelang district. The population used in the research were all employees of CV. Sakura Makmur Santoso with a total of 60 employees (respondents). The sampling technique is the non-probability sampling technique with the saturated sampling method. In this research using primary data, the method of data collection is by distributing questionnaires/questionnaires. This research is a quantitative research, the approach used is multiple linear regression. The results of this research indicate that work discipline, job description, and work facilities have a positive and significant influence partially/directly on employee work performance as evidenced by the t value of the variable X1 X2 X3 > from t table (2.003) and the sig value on the variable X1 X2 X3 < 0.05, and the results of this research have a positive and significant simultaneous effect on the work performance of CV Sakura Makmur Santoso employees with a calculated F value of 25.824 > from F table of 2.76 and a significance value of 0.000 < 0.05.